2010
DOI: 10.4315/0362-028x-73.9.1658
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Concentration in Milk Sampled from Canadian Farms

Abstract: A study was conducted to determine the iodine concentration in milk and the relationship between that concentration and milking and feeding management practices. Milk samples were collected from the bulk tanks of 501 farms in all provinces of Canada. With a view to obtaining further information about farm management, a questionnaire was completed at each of the selected farms. Total iodine concentration (organic and inorganic) in the milk was determined using inductively coupled plasma mass spectrometry. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
3
16
2
1
Order By: Relevance
“…Iodine is an essential component of thyroid hormones necessary for thyroid function . Although the iodine concentration of milk varies widely within and between countries, depending on the iodine content of water, soil, and animal feed, season, and use of iodine as a disinfectant of udders and milking tools, studies in many countries have found that cow's milk is a relevant source of dietary iodine . In France, dairy was the source of 40% of dietary iodine in children and adolescents, while milk alone supplied 18% .…”
Section: Dairy Product Consumption and Key Nutrient Intake And Statusmentioning
confidence: 99%
“…Iodine is an essential component of thyroid hormones necessary for thyroid function . Although the iodine concentration of milk varies widely within and between countries, depending on the iodine content of water, soil, and animal feed, season, and use of iodine as a disinfectant of udders and milking tools, studies in many countries have found that cow's milk is a relevant source of dietary iodine . In France, dairy was the source of 40% of dietary iodine in children and adolescents, while milk alone supplied 18% .…”
Section: Dairy Product Consumption and Key Nutrient Intake And Statusmentioning
confidence: 99%
“…Milk iodine levels for the farms in the low and high groups were compared with the same farms' values reported in the previous study (Table 3 in Borucki Castro et al, 2010). For the high group, milk iodine concentration did not differ significantly between the 2 years (2007 and 2008), showing that the elevated iodine content in the milk on some farms was not circumstantial, as the same farms still produced milk with elevated iodine content a year later.…”
mentioning
confidence: 68%
“…The farms for this study were selected based on milk iodine concentrations recorded in a previous study (Borucki Castro et al, 2010). Of the 200 dairy farms that had been sampled in the province of Quebec (Canada), 30 farms with the highest iodine levels (high group) and 30 farms with lowest iodine levels (low group) were chosen.…”
mentioning
confidence: 99%
“…In addition to iodized table salt, dairy products have been cited as a major source of dietary iodine in most developed societies (WHO ; Norouzian and others ). The iodine level in dairy products can vary widely depending on the level of iodine in soil and vegetation consumed by dairy cattle (Berg ; Borucki and others ).…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, milk iodide levels less than 500 μg/L are considered acceptable for human consumption (WHO ). As milk levels of iodide fluctuate considerably, both within and between farms, there have been renewed concerns that use of iodine‐based pre‐milking and post‐milking teat disinfectants significantly contribute to high or too high levels of iodide level in milk (Borucki Castro and others , ).…”
Section: Introductionmentioning
confidence: 99%